Globalization and Labour in the Asia Pacific Region - Sharma, Basu (Relations industrielles / Industrial Relations, 2001)
Globalization and Labour in the Asia Pacific Region, edited by Chris Rowley and John Benson, is reviewed.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Deregulation; Globalization; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z